Predictive validity of state versus trait challenge and boredom for career aspirations. (October 2022) - Krannich, Maike; Goetz, Thomas; Roos, Anna-Lena; Murayama, Kou; Keller, Melanie M.; Bieg, Madeleine; Lipnevich, Anastasiya A.
Abstract: This study focused on students' perceived challenge, its direct links to career aspirations along with indirect links to career aspirations via boredom. We extended previous findings by differentiating state and trait assessments of challenge and boredom and by investigating within- and between-person relations. We hypothesized overchallenge to go along with reduced career aspirations. Furthermore, boredom should occur due to both over- and underchallenge and should reduce those aspirations. We expected stronger effects of trait challenge and boredom on career aspirations as compared to the respective state reports. The hypotheses were tested in a sample of N  = 753 high-school students ( M age  = 15.72) from 43 classes by a questionnaire and an experience-sampling approach. Multilevel analyses showed overchallenge being linked to reduced career aspirations; this direct effect was equally strong for trait and state reports. Furthermore, the indirect effect of trait non-optimal challenge (over- or underchallenge) indicated a decrease in career aspirations via trait boredom. Highlights: Students' over- and underchallenge in mathematics are positively related to boredom. The relation between challenge and boredom is significant within- and between-person. Students' habitual trait boredom is negatively related to their career aspirations. Trait and state overchallenge are negatively related to career aspirations. The effect of trait over- and underchallenge on career aspiration is mediated by trait boredom.